Scholarship on the Popular Unity in Chile since 2000. Are historians lagging behind?. (1st June 2021) - Del Pozo Artigas, José; Monsálvez Araneda, Danny; Valdés Urrutia, Mario
Abstract : This article examines the questioning indicated by some historians at the beginning of the twenty-first century regarding that they would be in debt to the study of the Allende government and the Popular Unity (UP) in Chile (1970–3). Although historians have investigated the diverse issues and problems of that period in varying depth, there are topics that have not been fully addressed: for example, the relationship between socialists, communists and President Allende, and the participation of left-wing women, native people and youth in the referred historical process. However, this work addresses the contributions on the subject made mainly by Chilean authors in books and articles on UP, namely: general studies on the period, works concerning Allende and some of his close collaborators, the economic changes that affected national and international private interests, some of the forces of the Left and Right (parties and movements), popular social sectors, the state coup, the military, culture and the press. A novel aspect in a significant number of these works is the use of interviews with witnesses who played a significant role in, or lived through, the UP period.